Tam Model on Digi Banking BJB in Bandung - Fitri Anggraeni, Annisa; Rismunandar, Ichsan; Ahada, Roby; Lasminingrat, Anne; Candra Devi, Meita (Siber International Journal of Digital Business (SIJDB), 2025)
The purpose of this research is to know the perceived usefulness, perceived ease of use, attitude towards using and behavioral intention to use the DIGI app and also to understand the influence of perceived usefulness and perceived ease of use on attitude towards using and its implication on behavioral intention to use. The type used in this research is descriptive and comparative. The research type is descriptive survey and explanatory survey with quantitative method. The sampling technique used in this research is non-probability sampling in the form of accidental sampling by distributing questionnaires through Google Form. The tool that was used for data analysis is IBM SPSS Statistics 25. The result of this research shows that perceived usefulness, perceived ease of use, attitude towards using and behavioral intention to use the DIGI app is said to be quite good. Perceived usefulness and perceived ease of use simultaneously and partially influenced attitude towards using and behavioral intention to use significantly while attitude towards using influenced behavioral intention to use significantly.